PENGEMBANGAN POTENSI ANAK USIA DINI MELALUI PROSES PENDIDIKAN - Khulusinniyah, Khulusinniyah (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2025)
Humans will experience stages in their lives, as explained in the Qur’an. At each stage/level of life, they require stimulation and educational processes that are expected to develop the basic potential they have had since birth. Humans are born with diverse potentials, and in this regard, the educational process plays a very important role in developing those potentials. The role of parents and educators is crucial in shaping a child to become who they are, how their character develops, and in determining their future. The researcher chose library research as the method in this study, so the data sources used are books and journals that discuss the potential children bring from birth and the process of developing that potential